Narcolepsy Following Yellow Fever Vaccination: A Case Report - Rosch, Richard E.; Farquhar, Michael; Gringras, Paul; Pal, Deb K. (Frontiers in Neurology, 2016)
Narcolepsy with cataplexy is a rare, but important differential diagnosis for daytime sleepiness and atonic paroxysms in an adolescent. A recent increase in incidence in the paediatric age-group probably linked to the use of the Pandremix influenza vaccine in 2009, has increased awareness that different environmental factors can ‘trigger’ narcolepsy with cataplexy in a genetically susceptible population. Here we describe the case of a 13 year-old boy with narcolepsy following yellow-fever vaccination. He carries the HLA DQB1*0602 haplotype strongly associated with narcolepsy and cataplexy. Polysomnography showed rapid sleep onset with rapid eye movement (REM) latency of 47 minutes, significant sleep fragmentation and a mean sleep latency of 1.6 minutes with sleep onset REM in 4 out of 4 nap periods. Together with the clinical history, these findings are diagnostic of narcolepsy type 1. The envelope protein E of the yellow fever vaccine strain 17D has significant amino acid sequence overlap with both hypocretin and the hypocretin receptor 2 receptors in protein regions that are predicted to act as epitopes for antibody production. These findings raise the question whether the yellow fever vaccine strain may, through a potential molecular mimicry mechanism, be another infectious trigger for this neuro-immunological disorder.